Factors affecting the semen quality of breeding bulls (Bangladesh Veterinarian, 2019)
This study aimed to investigate the effects of breed, age, scrotal circumference, Body Condition Score (BCS), season and nutrition on bull semen quality at breeding bull station of Ejab Alliance Limited, Thakurgaon, Bangladesh. A total of 777 ejaculates were collected from 25 bulls (Holstein-Friesian-10; Sahiwal-15). All semen parameters were significantly (P4.5 years). Scrotal circumference significantly (P